The fungal H(+)-ATPase from Neurospora crassa reconstituted with fusicoccin receptors senses fusicoccin signal. - Marra, M (1995)
Fusicoccin affects several physiological processes regulated by the plasma membrane H(+)-ATPase in higher plants while other organisms having P-type H(+)-ATPases (e.g., fungi) are fusicoccin-insensitive. We have previously shown that fusicoccin binding to its receptor is necessary for H(+)-ATPase stimulation and have achieved the functional reconstitution into liposomes of fusicoccin receptors and the H(+)-ATPase from maize. In this paper we show that fusicoccin sensitivity can be conferred on the H(+)-ATPase from Neurospora crassa, a fungus insensitive to fusicoccin. In fact, H+ pumping by purified H(+)-ATPase from Neurospora crassa reconstituted into liposomes containing crude or partially purified fusicoccin receptors from maize was markedly enhanced by fusicoccin. The stimulation of H+ pumping by fusicoccin is dependent upon pH, fusicoccin, and protein concentration, as was reported for the system reconstituted with both proteins from maize.